Evaluation Of Crack On Arch Structures Using The Digital Image - Chan, Yi Zhe (Universiti Sains Malaysia, 2021)
This dissertation presents the usage of the Digital Image Correlation (DIC) technique in the determination of strain distribution on concrete arch structures to detect and predict the cracks on the structural surface. This study aims to develop the strain distribution on the concrete arch by applying a load on the structure. The results of this project are obtained via experimental works. Digital image correlation technique (DIC) is a high-precision, nondestructive, non-contact optical method that has been widely used in various fields for measuring surface deformation. One control sample was cast and tested to get the ultimate capacity of the concrete arch. The arch failed at around 22 kN of concentrated load at the midspan. Three experimental samples were tested at three load stages, such as 30% and 60% of the maximum load, and then, at the final loading stage, the samples were tested until failure. The loading was repeated three times at every loading stage. Data from LVDT are compared with the values obtained from GOM Correlate, a DIC software to validate the DIC results before carrying out DIC analysis. With more accurate data obtained from DIC, the prediction of crack’s location and pattern can be done on the structural surface and the work in structural health monitoring can be more focused on using image analysis so that it can reduce the cost, risk, and limitation to the individual who does the works. From the results of the experiment, the location of the crack at failure can be predicted with a high level of accuracy by analyzing the strain on the specimen surface. The strain distribution on the structure gives a clear vision of where the highest strain and stress are accumulated during the deformation process and hence the prediction of the crack path can be made. The results also showed that the prediction made at 60% of the maximum load is more accurate than the prediction made at 30%.